Pakistan Japan Relations and Prospects for Peace and Development in South Asia - Dr. Salma Malik (CISS Insight Journal, 2014)
In case of South Asia, regionalism in the true sense is yet to gain full momentum. Despite the realization about rising security concerns, albeit of non-traditional nature, the region remains heavily entrapped by long standing traditional problems. Dubbed as a potential nuclear flashpoint, the reasons for enmity often outweigh the incentives for amity in the region. Host to one fourth of the world’s population, an alarming number of which lives below the poverty line, the region has not only inherited quite a few traditional problems, such as a flawed legacy of partition; disputed territories, contested borders, sharing of river waters as well as nuclear arms racing which stand in the way of regional cooperation and make the security dilemma more seamless and intractable. The relations between individual member states of South Asia and extra regional actors have traditionally been very good, but major international actors, have often played an important role as conflict mediators as well as developmental partners for countries in the region. In this capacity, Japan as a champion of global disarmament, pacifism and economic development has, through its positive diplomacy and soft power potential mainly through economic interaction, enjoyed immense good will and strong relations with individual SAARC members including Pakistan. The post WW-II environment, provided both Japan, emerging from a very traumatic post war experience as well as the newly independent South Asian countries, such as India, Pakistan and others to enter into a positive relationship which, as mentioned above, had chiefly been economic in nature. It has been commonly believed that Pakistan Japan economic relations have mostly been one sided, with Japan investing and aiding Pakistan a lot more than gaining in return, however, contrary to this popular belief, both countries have, enjoyed a healthy and mutually beneficial relationship in the last few decades.